Automating Scientific Paper Screening with Backus-Naur Form (BNF) Grammars - Bucea Manea Tonis, Radu (Didactica Danubiensis, 2024)
This article explores BNF grammars to streamline the automated screening of scientific papers. BNF grammars define the valid structures and sentence formats for a specific language. They act like a rulebook, ensuring consistency and allowing for analysis of elements within the language. In this case, the BNF grammar serves as a blueprint for the proper formatting of scientific papers according to publisher guidelines. The grammar defines the acceptable structure and arrangement of elements like preamble, body, and paragraphs. By leveraging a tool like Java ANTLR v.4 runtime, we can convert the BNF grammar into a custom parser. This parser can then automatically assess submitted scientific papers, verifying if they adhere to the defined formatting rules established by the BNF grammar. This approach offers a way to automate the initial screening process for scientific papers, potentially saving time and improving consistency during the review process.